The Application of Nano-MoS(2) Quantum Dots as Liquid Lubricant Additive for Tribological Behavior Improvement - Guo, Junde (Nanomaterials (Basel), 2020)
Molybdenum disulfide quantum dots (MoS(2) QDs) are a promising lubricant additive for enhanced engine efficiency. In this study, MoS(2) QDs were used as lubricating oil additives for ball-on-disc contact and had adequate dispersity in paroline oil, due to their super small particle size (~3 nm). Tribological results indicate that the friction coefficient of paroline oil with 0.3 wt.% MoS(2) QDs reached 0.061, much lower than that of pure paroline oil (0.169), which is due to the formation of a stable tribo-film formed by the MoS(2), MoO(3), FeS, and FeSO(4) composite within the wear track. Synergistic lubrication effects of the tribo-film and ball-bearing effect cooperatively resulted in the lowest friction and wear.